MON-614 Lipid Profile In Patients With Primary Hypothyroidism: Does TSH Values Make A Difference? - Martins Machado, Catarina (J Endocr Soc, 2019)
Introduction: Thyroid hormones have an important role in the regulation of lipid metabolism. Higher levels of TSH could be associated with impaired lipid profile and cardiovascular disease, even with normal levels of free thyroxine (FT4). The aim of this study was to investigate the association between TSH levels and lipid profile in patients with primary hypothyroidism. Materials and methods: Retrospective evaluation of patients with primary hypothyroidism treated with levothyroxine (LT4), with normal levels of FT4. Patients with known dyslipidemia were excluded. Thyroid function, total cholesterol (TC), triglycerides (Tg), HDL-cholesterol (HDL) and LDL-cholesterol (LDL) were studied. Patients were divided according to their TSH levels: <2.5 uUI/mL (group 1), 2.5 ≤TSH< 5.0 uUI/mL (group 2) and ≥5.0 uUI/mL (group 3). IBM SPSS Statistics® software was used for statistical analysis; p level <0.05 was considered statistically significant. Results: We included 126 patients, 88.1% female, with mean age 46.1±14.1 years. The majority had auto-immune hypothyroidism (n=65, 51.6%) followed by post-surgical hypothyroidism (n=43, 34.1%). Mean TC levels were 180.7±35.2mg/dL, LDL levels 105.3±26.6mg/dL and Tg levels 100.1±47.9mg/dL. For higher TSH values, there was an increase in mean TC levels (group 1: 168.9mg/dL, group 2: 187.4mg/dL, group 3: 198.4mg/dL, p<0.001), mean LDL levels (group 1: 98.5mg/dL, group 2: 117.9mg/dL, group 3: 119.8mg/dL, p=0.003) and mean Tg levels (group 1: 86.1mg/dL, group 2: 104.5mg/dL, group 3: 119.9mg/dL, p=0.002). Between patients in group 1 and 3 there was a significant difference in serum TC, LDL and Tg levels (p<0.001, p=0.001 and p=0.001, respectively). Patients with hypothyroidism following thyroidectomy for malignant disease had significantly lower median TSH values compared to other types of hypothyroidism (1.1uUI/mL vs 3.0uUI/mL, p=0.003) and had lower mean TC values (174.2mg/dL vs 181.7mg/dL, p>0.05) and lower mean LDL levels (96.3mg/dL vs 106.7mg/dL, p>0.05). TSH values positively correlated with higher TC levels (r=0.319, p<0.001), LDL levels (r=0.267, p=0.003) and Tg levels (r=0.264, p=0.003). Conclusions: Serum lipid levels were higher among patients with higher TSH values, especially in those with TSH ≥5.0 uUI/mL, suggesting that subclinical hypothyroidism may be associated with mild dyslipidemia. Even though there is insufficient evidence to recommend treatment with LT4 to achieve low-normal TSH values in order to accomplish better lipid control, it may be beneficial in high risk patients. It would be interesting to evaluate lipid profile following an increase in LT4 dose, in order to better understand the effect of levothyroxine in these patients.